PEMANFAATAN SISA PECAHAN CAMPURAN BETON SEBAGAI PENGGANTI AGREGAT KASAR PADA LASTON WEARING COURSE GRADASI KASAR - Yamsasmi, -; AS, Syafaruddin; Azwansyah, Heri (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2017)
Making as asphalt mixture requires a huge amount of aggregates because its structure contains 90-95% of aggregates. One of the many materials that are mostly used is gravel. Continuoes use of gravel in large amounts will have an impact on the environment where the gravel is obtained. On the other hand, the high levels of infrastuctrural construction out of concrete in Kalimantan barat aspecially in Pontianak allows the possitility of structural failure, fire and precast concrete failures to increase. Therefore, the use of concrete shards to substitute coarse aggregates becomes an alternative in this research. This research uses the experiment method of comparing between the use of course aggregates and the use of K-225 and K-300 concrete sherds with the varielies of asphalt grudes at 5,0%,  5,5%,  6,0%, 6,5%, 7,0%. We use a total of 45 sampels with each variely of course aggregates gotting 15 samples.we tested each samples using the marshall method so we get the marshall characteristics and optimum asphalt content of the mixture. Refrens of the bina marga 2010 specification. Based on marshall test, the parameters of marshall that meet the stability value at 5.0% - 7.0% asphalt content for the three types of mixture of the highest stability value occurred on the natural broken stone of 7.0% asphalt content of 2822.5kg. Flow value at 6.0% and 6.5% asphalt level of 3.767mm and 3.733mm for natural broken stone, 6.0% for 3.73mm for concrete mixture of K225, and for fractionation of K300 5%, 5.5% and 6.5% concrete mixture of 2.77mm, 3.73mm, and 2.80mm. VIM values for the three mixtures at 7.0% asphalt content of 4.460% natural broken stone, 4.57% of K225 concrete mixed fractions, and 4.31% for K300 concrete mixed fractions. The value of FVB for natural crushed stone at 6.5% and 7.0% asphalt content of 76.116% and 81.538%, 6.0% - 7.0% by 69.92%, 79.87%, and 90.66% for concrete mixture of K225 mixture, and concrete mixture of K300 5.5% 7.0% by 65.81%, 71.17%, 74.31%, and 87.72%. the MQ values for the three mixed types meet the standards but at 5.5% asphalt content of 223.80 kg / mm for the fractional mixture of K225 concrete does not meet. From the data analysis, the optimum bitumen content (KAO) was obtained for the mixture of crude aggregate aggregate of 6.54%, the coarse aggregate of K225 concrete mixture was 6.05%, and the crude aggregate of K300 concrete mixture was 6.65%.     Key words: Asphalt Concrete Wearing Course , mixed concrete mixture, Marshall Characteristic, Coarse Gradation